2021
DOI: 10.1111/nph.17427
|View full text |Cite
|
Sign up to set email alerts
|

HEXOKINASE1 signalling promotes shoot branching and interacts with cytokinin and strigolactone pathways

Abstract: Plant architecture is controlled by several endogenous signals including hormones and sugars. However, only little information is known about the nature and roles of the sugar signalling pathways in this process. Here we test whether the sugar signalling pathway mediated by HEXOKINASE1 (HXK1) is involved in the control of shoot branching.To test the involvement of HXK1 in shoot branching and in the hormonal network controlling this process, we modulated the HXK1 pathway using physiological and genetic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 102 publications
(178 reference statements)
2
67
0
Order By: Relevance
“…Studies have shown that HXKs play an important role in different stages of plant development [35]. The mechanism by which HXK affects all stages of the plant life cycle may lie in the regulation of glucose abundance signals in several hormone signaling pathways, such as the auxin (AUX) [46], cytokinin (CK) [47], abscisic acid (ABA) [44], gibberellic acid (GA) [48], and brassinosteroid (BR) [49] pathways and even the growth regulator melatonin (MT) pathway [35]. Overexpression of OsHXK5, OsHXK6, or their noncatalytic mutant alleles in high-glucose media can restore the glucose-sensitive seedling development-arrested phenotype in Arabidopsis gin2-1 plants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that HXKs play an important role in different stages of plant development [35]. The mechanism by which HXK affects all stages of the plant life cycle may lie in the regulation of glucose abundance signals in several hormone signaling pathways, such as the auxin (AUX) [46], cytokinin (CK) [47], abscisic acid (ABA) [44], gibberellic acid (GA) [48], and brassinosteroid (BR) [49] pathways and even the growth regulator melatonin (MT) pathway [35]. Overexpression of OsHXK5, OsHXK6, or their noncatalytic mutant alleles in high-glucose media can restore the glucose-sensitive seedling development-arrested phenotype in Arabidopsis gin2-1 plants.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from SnRK1 and TOR, hexokinase 1 (HXK1) over-expressing plants showed loss of apical dominance [436]. It was confirmed in rose, pea and Arabidopsis that HXK1 promotes shoot branching [437]. These findings show that sugar signaling events control branching of vegetative shoots and inflorescences.…”
Section: Developmental Regulation By Sugar Signalingmentioning
confidence: 85%
“…Sugars not only provided energy but also acted as a signal for bud outgrowth [ 50 , 51 ]. CTKs up-regulated the genes responsible for the sugar sink strength in previous studies.…”
Section: Discussionmentioning
confidence: 99%